Explanations of a magic trick across the life span - Olson, Jay A.; Demacheva, Irina; Raz, Amir (Frontiers in Psychology, 2015)
Studying how children and adults explain magic tricks can reveal developmental differences in cognition. We showed 167 children (aged 4 to 13 years) a video of a magician making a pen vanish and asked them to explain the trick. Although most claimed to know the secret, none of them correctly identified it. The younger children provided more supernatural interpretations and more often took the magician’s actions at face value. Combined with a similar study of adults (N=1008), we found that both young children and older adults were particularly overconfident in their explanations of the trick. Our methodology demonstrates the feasibility of using magic to study cognitive development across the life span.